Pain-to-hospital times, cardiovascular risk factors, and early intrahospital mortality in patients with acute myocardial infarction - Brković E; Novak K; Puljak L (Dove Medical Press, 2015)
Eliana Brković,1 Katarina Novak,2,3 Livia Puljak3 1Department of Psychiatry, 2Department of Internal Medicine, Division of Cardiology, 3Laboratory for Pain Research, University of Split School of Medicine, Split, Croatia Background: The aim of the study was to analyze the most recent trends in myocardial infarction (MI) care, the number of patients treated for MI and their outcomes, cardiovascular disease risk factors, and pain-to-hospital times in MI patients. Subjects and methods: For 778 patients treated for acute MI at the Coronary Care Unit (CCU) of University Hospital Split, Croatia the following data were acquired: outcome during hospitalization (survived, deceased), cardiovascular risk factors (hypertension, diabetes, dyslipidemia, previous MI, smoking), and pain-to-CCU time. Results: Among 778 patients treated for acute MI, there were 291 (37%) women and 487 (63%) men. Forty-five patients (6%) died during hospitalization, mostly due to cardiogenic shock. An association was found between early intrahospital mortality and the following risk factors: age >70 years, female sex, previous MI, and smoking. Median pain-to-call time was 2 hours, and median time from the onset of pain to arrival into the CCU was 4 hours. There were 59 (7.6%) patients admitted to the CCU within recommended 90 minutes. Diabetic comorbidity was not associated with early death or with longer time from pain to emergency calls. Conclusion: Some of the risk factors associated with adverse outcomes in MI are modifiable. Prehospital delay of 4 hours observed in patients who suffered an MI is too long, and more effort should be devoted to investments in health care and education of the general public regarding chest pain symptoms. Keywords: prehospital delay, ischemic heart disease